STRATEGI PEMBELAJARAN MODEL INKUIRI JURISPRUDENSI UNTUK PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI SEKOLAH MENENGAH ATAS - Sumarno Sumarno (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstrac:Pendidikan Pancasila dan Kewarganegaraan in secondary education aimed at developingthe potential of learners in all dimensions of citizenship, which include: civic confidence, civiccommitment, and civic responsibility. These objectives can be realized by implementing a learningstrategy JurisprudentialInquiry model. JurisprudentialInquiry model is a design study that was createdand developed by Donald P. Oliver and James Shaver to help students learn to think criticallysystematic, tolerant, caring and able to determine the position of the various controversies attitudestoward contemporary issues of public policy that is going on in the life society and state. The resultsshowed that students’ academic achievement group that learned with a higher inquiry strategy withthat learned with conventional learning.Keywords: civic education and the jurisprudential inquiry model